Analysis of the predictive effect and feedback control in an extended lattice hydrodynamic model. Issue 5 (10th January 2020) - Li, Lixiang; Ge, Hongxia; Cheng, Rongjun
Abstract : Purpose: This paper aims to put forward an extended lattice hydrodynamic model, explore its effects on alleviating traffic congestion and provide theoretical basis for traffic management departments and traffic engineering implementation departments. Design/methodology/approach: The control method is applied to study the stability of the new model. Through nonlinear analysis, the mKdV equation representing kink-antikink soliton is acquired. Findings: The predictive effect and the control signal can enhance the traffic flow stability and reduce the energy consumption. Originality/value: The predictive effect and feedback control are first considered in lattice hydrodynamic model simultaneously. Numerical simulations demonstrate that these two factors can enhance the traffic flow stability.